Structure set in stone: designing rigid linkers to control the efficiency of intramolecular singlet fission - Ahrens, Lukas; Wollscheid, Nikolaus; Han, Jie; Kefer, Oskar; Rominger, Frank; Roozbeh, Ashkan; Freudenberg, Jan; Dreuw, Andreas; Bunz, Uwe H. F.; Buckup, Tiago (The journal of physical chemistry. B, Biophysics, biomaterials, liquids, and soft matter, 2021)
Research on materials facilitating efficient singlet fission (SF) is driven by a possible reduction of thermalization losses in organic photovoltaic devices. Intramolecular SF (iSF) is in this context of special interest, as the targeted modification of either chromophores or linkers enables gradual variations of molecular properties. In this combined synthetic, spectroscopic, and computational work, we present and investigate nine novel spiro-linked azaarene dimers, which undergo efficient iSF with triplet yields up to 199%. Additional molecular braces enhance the rigidity of these tailor-made dimers (TMDs), resulting in great agreement between crystal structures and predicted optimal geometries for iSF in solution. Regardless of the employed chromophores and linkages, the dynamics of all nine TMDs are perfectly described by a unified kinetic model. Most notably, an increase in the orbital overlap of the π-systems by decreasing the twist angle between the two chromophores does not only increase the rate of formation of the correlated triplet pair but also further promotes its decorrelation. This new structure-function relationship represents a promising strategy toward TMDs with high triplet lifetimes to be utilized in optoelectronic devices.